Handbook of vegetable preservation and processing - Hui, Y. H. (Marcel Dekker, 2011)
Representing the vanguard in the field with research from more than 35 international experts spanning governmental, industrial, and academic sectors, the Handbook of Vegetable Preservation and Processing compiles the latest science and technology in the processing and preservation of vegetables and vegetable products. This reference serves as the only guide to compile key tools used in the United States to safeguard and protect the quality of fresh and processed vegetables. A vast and contemporary source, it considers recent issues in vegetable processing safety such as modified atmosphere packaging, macroanalytical methods, and new technologies in microbial inactivation.